Comparison Between High-Tech and Non-High-Tech Sharia Companies in Indonesia: Komparasi Antara Perusahaan Syariah Kategori High-Tech dan Non High-Tech di Indonesia - Sil Avin Arlaili; Imelda Dian Rahmawati (Academia Open, 2023)
This study aims to examine and determine the significant difference between the internet financial reporting index of Islamic companies in the high-tech and non- high-tech categories in companies listed on the IDX JII Index in 2014-2018. This research method uses quantitative methods, using all data from the Indonesia Stock Exchange, especially Islamic companies listed on the IDX JII Index. Sampling companies use purposive sampling method and analysis of IFR components, calculate the IFR value, classify the type of company and the T Different test (Independent Samples Test). The results of this study indicate that high-tech and non-high-tech companies have a significant value of 0.025 > 0.05, meaning that there is a significant difference between companies in the high-tech and non-high-tech categories in Islamic companies listed on the JII Index. BEI 2014-2018. Highlights: Significance of the study: The study aims to determine the significant difference in the internet financial reporting index between high-tech and non-high-tech Islamic companies listed on the IDX JII Index. This highlights the importance of understanding the online reporting practices of different types of companies in the Islamic finance sector. Methodology: The study employs quantitative methods, utilizing data from the Indonesia Stock Exchange and applying the independent samples t-test to analyze the internet financial reporting components and calculate the index value. The purposive sampling method is used to select the companies for the study, ensuring a representative sample. Findings: The research findings indicate a significant difference (p-value of 0.025) between high-tech and non-high-tech Islamic companies in terms of their internet financial reporting index. This suggests that the level of online reporting varies between the two categories, emphasizing the need for tailored approaches in assessing and improving internet financial reporting practices. Keywords: Internet financial reporting index, Islamic companies, High-tech and non-high-tech categories, IDX JII Index, Quantitative methods